ENGLISH CONTAINER METAPHORS OF EMOTIONS IN UKRAINIAN TRANSLATIONS - Liudmyla Kovalenko; Alla Martynyuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
This study presents the results of comparative analysis of linguistic instantiations of English CONTAINER metaphors of emotions and their Ukrainian translations to reveal the cognitive models and cognitive operations that underpin the translations. The research data includes 2,000 utterances with CONTAINER metaphors of emotional states that come from G. Martin's novels and their translations into Ukrainian performed by V. Brodovyj. Ukrainian translations of the English EMOTION as CONTAINER mapping are based on three cognitive operations: reconstruction, substitution and elimination. There are some structural differences in linguistic instantiations of the EMOTION as CONTAINER mapping in the original and translation stemming from the analytical nature of English and synthetic nature of Ukrainian. If English CONTAINER metaphors are verbalised predominantly syntactically, by prepositional phrases, Ukrainian CONTAINER metaphors are verbalised mostly morphologically, by derivative words with the prefixes, etymologically connected to the idea of a CONTAINER. As for semantic differences, in Ukrainian translations EMOTIONS-BOUNDARIES mappings tend to be substituted with EMOTIONS-INTERIORS mappings. It implies an inference that Ukrainians imagine EMOTIONAL STATES as SUBSTANCES filling the insides of their bodies rather than BOUNDARIES suppressing them from the outside. Another tendency is substituting the CONTAINER as a STATIC PASSIVE ENTITY with some ACTIVE AGENT like a HUMAN / LIVING BEING influencing the EXPERIENCER.